Bifacial Photovoltaics : technology, applications and economics - Libal, Joris; Kopecek, Radovan (IET energy engineering series, 2018)
This book begins with an introduction to bifacial solar cells and goes on to look at design, characterisation, reliability; energy yield prediction simulation models; PV systems and yield data (bifacial gain); levelized cost of PV-generated electricity; PV technologies market introduction and their bankability; geographic location and environmental conditions relating to bifacial gain; and prospects for the future.